Bovine Bone Hidroksiapatite Materials Mechanics Properties at 900°C and 1200°C of Calcination Temperature - Antonius Adi Hendra Saputra; Joko Triyono; Teguh Triyono (Mekanika: Majalah Ilmiah Mekanika, 2017)
The aims of this study is to determine the mechanical characteristics of the calcinated scaffold material bovine hydroxyapatite (BHA) for bone filler applications. Scaffold BHA was obtained from femur section of bovine bones which cut into 10x10x10 mm. Scaffold BHA was calcinated by temperature variations of 900ºC and 1200°C for 2 hours with 10ºC/min as the amount of the increasing level. The study result of each scaffold BHA which had been calcinated by 900°C and 1200°C has a hardness value of 8.48 ± 0.1118 VHN and 12.37 ± 0.5803, meanwhile the compressive strength value of each scaffold BHA samples is 3.03 ± 0.6764 MPa and 1.96 ± 0.3450 MPa. The porous on scaffold BHA samples calcinated by 900°C and 1200°C which had been observed by SEM had porous size that is not much different, it was ± 200-400 μm, the difference can be seen from the smaller porous size of the scaffold BHA calcination 1200°C compared to the porous size of scaffold BHA calcination 900°C.